Effects of combination therapy of a CDK4/6 and MEK inhibitor in diffuse midline glioma preclinical models - Tomita, Yusuke; Link, Gabrielle; Ge, Yi; Gold, Emma R. H.; Racanelli, Anna; Cardona, Herminio Joey; Romero, Megan; Gadd, Samantha; Watanabe, Jun; Uchida, Eita; Hashizume, Rintaro; Takata, Nozomu; et al. (PLOS ONE, 2025)
Background Diffuse midline glioma (DMG) is an incurable brain cancer without a single FDA-approved drug that prolongs survival. CDK4/6 inhibitors have been evaluated in children with DMG with limited efficacy. Since MAPK pathway activation is upstream of cell proliferation, we hypothesized that MEK inhibitors may increase the anti-tumor effects of CDK4/6 inhibitors. Here, we evaluated the efficacy of the CDK4/6 inhibitor ribociclib and the MEK inhibitor trametinib in human and murine DMG models to investigate combinational effects. Methods We conducted in vitro and in vivo assays using DMG cell lines from human patient-derived xenografts (PDX) and genetically engineered mouse (GEM) models. In vitro, we assessed synergy across human DMG lines. In vivo, we evaluated therapeutic effects with histological examinations, survival analysis, pharmacokinetic measurements, and RNA-sequencing analysis. Results In vitro, ribociclib and trametinib had variable synergistic effects against human DMG cell lines. In vivo, a five-day treatment with combination therapy in the GEM DMG model significantly decreased cell proliferation and increased apoptosis compared with the vehicle, with trametinib having mostly cytotoxic effects and ribociclib having primarily cytostatic effects. In addition, a 21-day treatment with combination therapy significantly prolonged mice survival compared with the vehicle in the GEM DMG model (median survival: 112 days vs. 71.5 days, log rank test p = 0.0195). In an orthotopic PDX model, combination therapy did not prolong mice survival compared with vehicle, ribociclib, and trametinib. LC/MS analysis showed adequate drug delivery across the blood-brain-barrier (BBB) into tumor tissue in both GEM and PDX models. Transcriptomic analysis in the GEM model suggests that combination therapy inhibited the MAPK pathway and inflammation. Conclusions Combination therapy with ribociclib and trametinib significantly prolonged survival in the GEM model but not in the PDX model, highlighting the importance of testing novel therapies in diverse models.